Multivariate Calibration Applied to the Simultaneous Spectrophotometric Determination of Ascorbic Acid, Tyrosine and Epinephrine in Pharmaceutical Formulation and Biological Fluids - Solhjoo, Aida; Khajehsharifi, Habibollah (Current Analytical Chemistry, 2016)
Background: Epinephrine (EP), ascorbic acid (AA) and tyrosine (TY) usually coexist together in human blood and are considered as important molecules for physiological processes in human metabolism. Thus, to determine these compounds in biological fluids, we need to develop sensitive, simple and rapid methods. Method: The simultaneous spectrophotometric determination of AA, EP and TY, at pH=7.0 using multivariate calibration techniques such as principal component regression (PCR), partial least squares (PLS) and their first derivative methods have been carried out. Results: Satisfactory results were achieved using first derivative-partial least squares. After optimization of all variables, the linear ranges for AA, EP and TY were 0.8-35.0, 1.0-72.01 and 1.0-145.0 μgmL-1, respectively. The detection limits for AA, EP and TY obtained 0.1, 0.35 and 0.28 μgmL-1, respectively. Principal component (NPC) for AA, EP and TY were 2, 3 and 3. Prediction error sum of squares (PRESS) for AA, EP and TY were 2.37, 0.91 and 2.57, respectively. The root mean square errors of Prediction (RMSEP) for AA, EP and TY were 0.35, 0.16 and 0.60 respectively. Conclusion: Good agreement between prediction and actual concentrations clearly indicates the utilization of this procedure for the simultaneous determination of AA, EP and TY in serum, plasma and urine samples and also for the determination of AA in vitamin c tablet and EP in epinephrine injection.
Keywords: tyrosine